Custom Modification of the Blom-Singer Tracheostoma Valve Housing - James C. Lemon, DDS,1 Jan S. Lewin, PhD,2 Jack W. Martin, DDS, MS,3 (Journal of Prosthodontics, 2003)
A technique is presented for modifying the Blom-Singer tracheostoma valve housing to improve peristomal skin adherence for hands-free tracheoesophageal speech production following total laryngectomy.